A Design of Rapid Pulsed Intelligent Charging Circuit - Zhang Lefang; Li Xiaohong; Ren Zhihong (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
As known that the traditional DC constant voltage charging equipment not only can cause the battery overcharge or insufficient charging, but also the charging time is too long. In the paper, based on the theory of pulse charging method and the design of the pulsed fast intelligent charging equipment is presented, the implementation of hardware and software process of the system is given out, the analysis of the results show that it can effectively prevent overcharge and low charge phenomenon in the charging process of battery.